Sexuality in adolescence: reality in a rural community - Josefine Busanello; Mara Regina Santos da Silva; Adriane Maria Netto de Oliveira (Rev Rene)
It is a matter of education for health developed within a group of adolescents, students of a public school in a rural community, addressing human sexuality. Objectively, they tried to indentify the meaning of the process of adolescence and issues of interest concerning sexuality, throughout this period in the community. The practice, inspired by the educational proposal of Paulo Freire, was developed in a small town in Rio Grande do Sul during four meetings in the fi rst half of 2006, with fourteen students. The meetings and material produced by students were recorded and analyzed based on the goals of the practice. The results showed the family, friends, religion and local culture, as important references for such youths. Nevertheless, the themes of interest do not differ from those of adolescents from urban areas. In fact, they just add the values that infl uence the perception of their sexuality.